Custom 3D-printed porous titanium augments for Paprosky type III acetabular defects: a case series combining biomechanical rationale with early clinical outcomes - Tengbin Shi; Wenming Zhang; Xinyu Fang (3D Printing in Medicine)
Abstract Background Severe acetabular bone defects (Paprosky type III) pose significant challenges for reconstruction and stable implant fixation. This study aimed to analyze the biomechanical properties and clinical safety of personalized 3D-printed porous titanium alloy reinforcement augments and evaluate their therapeutic efficacy in reconstructing these complex defects. Methods We reviewed three cases of Paprosky type III acetabular defects reconstructed using personalized 3D-printed porous titanium alloy augments. Finite element analysis (FEA) simulated the defects, utilizing a commercial augment as a control. Stress distribution within the augments, fixation screws, acetabular cups, and surrounding bone was analyzed under simulated single-leg standing (1 × body weight), walking (4 × BW), and jogging (6 × BW) loading conditions, with comparisons made to the control. Results Under all loading conditions, the peak stresses observed on the augment screws and acetabular cups in all three cases were lower than the buckling strength of titanium alloy and were consistently lower than those recorded in the control group. This indicates that the personalized augments provided stable support for acetabular cup fixation, aiding in the restoration of the hip rotation center and lower limb length. Conclusions Personalized 3D-printed porous titanium alloy augments demonstrate favorable biomechanical safety and clinical efficacy based on FEA and initial case review. For severe acetabular bone defects, these custom augments offer good initial stability, promoting bone integration for long-term fixation, and potentially reducing risks associated with cup loosening, dislocation, and periprosthetic fracture.